PELATIHAN PENERAPAN INOVASI DIGITAL DAN SERTIFIKASI HALAL PADA PELAKU UMKM KOTA CIREBON - Suzana, Anna; Sulistiowati, Lisa Harry; Fatimah, Siska Ernawati (Transpublika Publisher, 2022)
The community service aims to provide comprehensive training and mentoring in obtaining halal certification and mastering information technology to MSMEs located in the city of Cirebon. The activity was attended by 30 MSMEs and lasted for one day at the Faculty of Economics and Business, Universitas Swadaya Gunung Jati. Through this activity, the importance of understanding the procedures for halal certification registration and optimizing the use of innovative technology for MSMEs is emphasized. The results of this community service activity include increasing awareness among MSMEs about the importance of implementing halal certification in their business operations. They are also encouraged to actively register their business units in the halal certification process with LPPOM MUI, thus enhancing the credibility and competitiveness of their products in the market. In addition, through information technology training, MSMEs are able to utilize technological innovations on various social media platforms to expand their market reach. Therefore, this community service is not only aimed at improving the overall quality of MSME products, but also empowering them through understanding and mastery of halal certification procedures and the use of relevant information technology in the context of modern business.